Evaluation on thermochemical processes for bioenergy applications of Bambara groundnut shell (BGS), Shea Nut Shell (SNS), Shea Nut chaff (SNC), and Sweet Sorghum Stalk (SSS) - Ibrahim, Mustapha Danladi (2025)
Fossil fuel dependency, global threat, and energy crisis drive the need for an alternative and renewable energy source, that's cleaner and cost-effective. Alternative energy like biomass is renewable and remarkable with almost a zero-carbon footprint increasingly gaining attention amidst the environmental challenges of coal and fossil fuels. Bambara groundnut shell (BGS), Sweet Sorghum Stalk (SSS), Shea Nut chaff (SNC), and Shea Nut Shells (SNS) are an underutilized crop-biomass waste after cultivation readily available as industrial and agricultural biowaste for energy generation. This study focused on intermediate pyrolysis, catalytic co-pyrolysis and torrefaction. Firstly, the physicochemical and thermogravimetric analysis of the BGS before and after moisture removal at 105 ℃ for 4 h, coded UT (untreated) and PT (pre-treated), respectively. The coded investigated samples were untreated (UT1, UT2, and UT3) and pre-treated (PT1, PT2, and PT3), with particulate sizes as 1180, 600, and 300 µm, with additional two BG genotypes (BGS-G4 & BGS-G5). The results showed that BGS-UT1 (1180 µm) had the least ash content (AC) of 6.8 ± 0.5 wt. %, with maximum HHV of 18.6 ± 0.5 MJ/kg, activation energy of 21.00 kJ/mol and suitable pyrolysis temperature ≤ 650 ℃. The intermediate pyrolysis (IP) of BGS-G1, SSS, and SNS in a vertical tube reactor at 600 ℃, with an average heating rate ≥ 33.0 ℃/min. The pyrolysis oil and HHV yield was 38.0 ± 6.4, 44.2 ± 6, and 39.7 ± 5.2 wt. % and 23.7 ± 1.8, 23.8 ± 1.8, and 26.5 ± 2.0 MJ/kg for BGS-G1 SSS and SNS, respectively. The biochar recorded the highest HHV for SNS at 26.4 ± 1.8 MJ/kg. The effects of N2, CO2, and N2/CO2 (flue gas) in an IP experiment of BGS did not relatively affect the yields of bio-oil, biochar, and syngas, but had optimum gas flowrate at 17.5 min/s and bio-oil pH within 5.2–5.8 indicating minimum presence of acids in bio-oil. Their CHNS analysis of both bio-oil and biochar carbon content are within 50.04–60.49 wt. %. Intermediate catalytic co-pyrolysis was conducted for SSS and plastic (polypropylene (PP) over amphoteric catalysts (Al2O3, and 25%Ni/Al2O3), acidic catalysts (ZSM-5 and 25%Ni/ ZSM-5) ratios. The mixing ratio of SSS to PP (1:1) at 600 ℃, forming the least oxygenate from SSS (15.1 wt. %) and the highest oxygenate in PP (25.2 wt. %), respectively. The feed-to-catalyst, 25%Ni/Al2O3_0.25 (1:0.25) had the optimum bio-oil and HHV at 49.02 ± 0.26 wt. % and 41.1 ± 0.7 MJ/kg, respectively. The catalytic co-pyrolyzed in the presence of 25%Ni/Al2O3 yielded optimum of excellent C-H-containing FTIR functional groups and aliphatic hydrocarbon corroborated by GCMS analysis. GC-MS analysis categorized the bio-oils as ketones, furans, phenolics, acids, phenols, and benzene derivatives. Finally, wet torrefaction of Shea Nut Chaff (SNC) had an optimum yield (55.5 wt. %) and the least hydrophobicity at 260℃-W/B5R10 (45 bar), energy yield and HHV of 89.54 % and 15.81 MJ/kg. The best-fit model of ANOVA (analysis of variance) is 2FI, with p-values < 0.05, and R2 of 0.9443. In conclusion, the BGS, SSS, SNS and SNC provided liquid and solid fuels after being subjected to treatments to minimize the impact of global warming.